Psychosocial aspects of corruption, violence And the exercise of the power in Perú - Montero López, Víctor (2017)
Power is developed in various areas , the article shows the motivation of power, power in history, the relationship power and violence, power and groups , power and identity , discourse and addiction to power, the relationship power and sex , power dominated . And it concludes with an example of how similar corrupt characters is built Montesinos former adviser to Alberto Fujimori, in what is called "the little Montesinos".